Magnetic nanoparticles for components of MRI diagnostics and electronic devices - Korsakova, Alina S.; Kotsikau, Dzmitry A.; Livanovich, Kanstantsin S.; Shutava, Tatsiana G.; Haiduk, Yulyan S.; Pankov, Vladimir V. (Journal of the Belarusian State University. Physics, 2021)
The formation of single-phase solid solutions of iron oxide and manganese oxide with a spinel structure in MnxFe3 – xO4 system (x = 0; 0.3; 0.6; 0.8; 1.0; 1.2; 1.4; 1.8) has been established by methods of X-ray phase analysis and infrared spectroscopy. The maximum saturation magnetization was found for the composition Mn0.3 Fe2.7O4 (Ms = 68 A ⋅ m2 ⋅ kg−1 at 300 K and Ms = 85 A ⋅ m2 ⋅ kg−1 at 5 K), which is associated with a change in the cationic distribution over tetrahedral and octahedral voids. The materials obtained were stabilized in the form of colloidal solutions using a number of polyelectrolytes. It was found that poly(diallyldimethylammonium chloride) (PDDA) had the best stabilizing effect due to its structural features. A method for controlling the magnetic properties of magnetite by partial replacement of iron ions in the magnetite structure with manganese is proposed. Changing the magnitude of the magnetization and coercive force is possible by changing the degree of substitution. Relatively high values of specific magnetization, as well as uniformity of magnetic particles in size, can be of practical interest, for the manufacture of contrast agents in MRI diagnostics.